From Tarekat to Arab Community: the Islamization Process in Indramayu - Tabroni, Roni; Muhsin Z, Mumuh; Dienaputra, Reiza D; Mulyadi, R M (Paramita: Historical Studies Journal, 2020)
This research talks about the process of Islamization in Indramayu. The Islamization in Indramayu raises three main questions. The first question is, where was the arrival of Islam in Indramayu. Second, when is the appearance of Islam. Third, who has a role in the Islamization process. This research uses the historical method, which consists of four stages: heuristic, criticism, interpretation, and historiography. This method was then collaborated with Islamic social movement theory to analyze the ideology of leadership and movement mobility of the propagator group of Islam in Indramayu. The results showed that the arrival of Islam in Indramayu came from the port of Cimanuk. Then spread to various areas, including in the countryside. Second, Islam has been dating in Indramayu since the 15th century. Third, some communities play a role in Islamization in Indramayu. The communities were very influential until the 19th century. They consisted of the Arab community and the adherents of the tarekat, especially from Cirebon. The first order to develop was Syattariyah. Meanwhile, the Arabic community leader from Cirebon was Sayyid Abdur Rahman bin Muhammad Basy-Syaiban. He is a figure who originated from the Hadramaut in the early seventeenth century.Penelitian ini berbicara tentang proses islamisasi di Indramayu. Proses islamisasi di Indramayu memunculkan tiga pertanyaan utama. Pertanyan pertama adalah dari mama dan di mana kedatangan islam. Kedua, kapan waktu kedatangan Islam. Ketiga, siapa yang berperan dalam proses islamisasi. Untuk menjawab pertanyaan tersebut, penelitian ini menggunakan metode sejarah yang terdiri atas empat tahap: heuristic, kritik, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa kedatangan Islam di Indramayu berasal dari pelabuhan Cimanuk. Kemudian menyebar ke berbagai daerah, termasuk di pedesaan. Kedua, Islam telah dating di Indramayu sejak abad ke 15. Ketiga, terdapat komunitas yang berperan dalam Islamisasi di Indramayu. Komunitas tersebut sangat berpengaruh sampai abad ke 19. Mereka terdiri atas komunitas Arab dan para penganut tarekat, terutama dari Cirebon. Tarekat pertama yang berkembang adalah Syattariyah. Sementara itu, tokoh komunitas arab yang berasal dari Cirebon adalah Sayyid Abdur Rahman bin Muhammad Basy-Syaiban. Ia merupakan tokoh yang berasal dari Hadramaut pada awal abad ketujuh belas.